Change in carbon stable isotope ratios of the predatory bug Orius majusculus after dietary shifts. Issue 3 (30th July 2013) - Madeira, Filipe; Di Lascio, Antonella; Carlino, Pasquale; Costantini, Maria Letizia; Pons, Xavier
Abstract Orius majusculus Reuter (Hemiptera: Anthocoridae) is an important component of the pest predatory complex in arable crops in Mediterranean areas. It moves between crops searching for prey, and improving knowledge on its dispersal abilities will help to develop conservation biological control strategies. Stable isotope ratios may be used as a tool for tracking insect movements, as the isotopic composition of insect tissues changes to reflect that of their diet when they undergo dietary shifts on moving between isotopically distinct crops. We carried out laboratory diet switch experiments with a stable isotope approach to infer information on dispersal of O. majusculus individuals among C3 and C4 crops to better understand isotopic field data collections. Switching the aphid food source caused a quick change in δ13C signatures, regardless of the original and final food source. Changes in the δ13C ratio of O. majusculus after diet switching fitted with an exponential model that showed similar turnover rates, and thus half‐lives, between shifting diets up to 20 days. Subsequently, whereas individuals feeding on C4 aphids did not survive, turnover rate decreased in individuals that switched from C4 to C3 aphids. However, δ13C traces from the original source remained in the predator until 25 days after switching, and this is enough time to help determine the movement of O. majusculus between crops in the field and to plan the timing of predator sampling and crop practices that may enhance predator ecological services. Orius majusculus that switched to a maize aphid diet showed different turnover rates between sexes, although this did not influence the pattern of switchover.